Using Serology to Anticipate Measles Post-honeymoon Period Outbreaks. Issue 8 (August 2020) - Metcalf, C.J.E.; Wesolowski, A.; Winter, A.K.; Lessler, J.; Cauchemez, S.; Moss, W.J.; McLean, A.R.; Grenfell, B.T.
Abstract : Measles vaccination is a public health 'best buy', with the highest cost of illness averted of any vaccine-preventable disease (Ozawa et al ., Bull. WHO 2017;95:629). In recent decades, substantial reductions have been made in the number of measles cases, with an estimated 20 million deaths averted from 2000 to 2017 (Dabbagh et al ., MMWR 2018;67:1323). Yet, an important feature of epidemic dynamics is that large outbreaks can occur following years of apparently successful control (Mclean et al ., Epidemiol. Infect. 1988;100:419–442). Such 'post-honeymoon period' outbreaks are a result of the nonlinear dynamics of epidemics (Mclean et al ., Epidemiol. Infect. 1988;100:419–442). Anticipating post-honeymoon outbreaks could lead to substantial gains in public health, helping to guide the timing, age-range, and location of catch-up vaccination campaigns (Grais et al ., J. Roy. Soc. Interface 2008003B6:67–74). Theoretical conditions for such outbreaks are well understood for measles, yet the information required to make these calculations policy-relevant is largely lacking. We propose that a major extension of serological studies to directly characterize measles susceptibility is a high priority.